(untitled) (CIPEEX, 2025)
This abstract aims to analyze the characterization of slave-like work in Brazil, identify the conditions that configure this practice and evaluate the associated legal, social, economic and human impacts. It is also intended to clarify the role of the different spheres (administrative, civil and criminal) in monitoring and combating this form of exploitation. The method was conducted through a detailed review of MTP Normative Instruction No. 2/2021, which defines the conditions that characterize slave-like work. The established legal criteria, submission indicators and the performance of the responsible institutions were examined. Additionally, reports and data on inspections and legal actions related to the topic were reviewed. As a result, it appears that slave labor is a problem that has persisted since the beginning of the country’s history, resulting in serious legal, social, economic and, mainly, human consequences. The legal characterization of slave-like work is addressed by MTP Normative Instruction No. 2/2021, which defines five conditions that can occur alone or together: forced labor; exhausting journey; degrading working conditions; restriction of movement by any means due to debt with the employer, either at the time of hiring or during the employment contract; retention in the workplace due to restricted use of transportation; overt surveillance; seizure of documents or personal objects. It is concluded that slave-like work is a serious issue that affects several productive areas in Brazil, although it still receives little attention. Responsibility for combating slave labor occurs threefold: at the administrative level, the Ministry of Labor carries out inspections, prepares reports, issues infraction notices and enables defense. If the infraction is confirmed, the company is included in the list of condemned companies. In the civil sphere: The Public Ministry of Labor seeks an agreement through the Conduct Adjustment Term (TAC). If the employer refuses, a public civil action will be filed so that the company can defend itself. Criminal sphere: Brazilian legislation makes it a crime to keep workers in conditions similar to slavery, therefore liability will be imposed through criminal sanctions. Coordinated action between the administrative, civil and criminal spheres is crucial to eradicate this form of exploitation and protect workers’ rights. Continuing inspection efforts and strengthening prevention measures are essential to confront and mitigate the impacts of slave-like work.